Low-cost method for producing extreme ultraviolet lithography optics - MONTCALM CLAUDE; FOLTA JAMES A; TAYLOR JOHN S; SPILLER EBERHARD A (2003)
Spherical and non-spherical optical elements produced by standard optical figuring and polishing techniques are extremely expensive. Such surfaces can be cheaply produced by diamond turning; however, the roughness in the diamond turned surface prevent their use for EUV lithography. These ripples are smoothed with a coating of polyimide before applying a 60 period Mo/Si multilayer to reflect a wavelength of 134 Å and have obtained peak reflectivities close to 63%. The savings in cost are about a factor of 100.